2012
DOI: 10.5888/pcd9.120079
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Discharge Rates Before and After Implementation of a City-wide Smoking Ban in a Texas City, 2004–2008

Abstract: The objective of this study was to examine hospital discharge data on 5 tobacco-related diagnoses before and after implementation of a smoking ban in a small Texas city. We compared hospital discharge rates for 2 years before and 2 years after implementation of the ban in the intervention city with discharge rates during the same time in a similar city with no ban. The discharge rates for blacks and whites combined declined significantly after the ban in the intervention city for acute myocardial infarction (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 1 publication
0
24
0
2
Order By: Relevance
“…From having no U.S. state with a comprehensive smoke-free law in 2000, 26 U.S. states and the District of Columbia had implemented such laws in 2013 [6]. Such comprehensive smoke-free laws have been shown to benefit public health, and may have contributed to declines in SHS-associated conditions such as middle-ear infections, sudden infant death syndrome, and heart disease [2], [14], [15]. More so, in addition to achieving their primary objective of protecting nonsmokers from involuntary SHS exposure, such comprehensive smoke-free laws also denormalize smoking and may motivate smokers to quit.…”
Section: Discussionmentioning
confidence: 99%
“…From having no U.S. state with a comprehensive smoke-free law in 2000, 26 U.S. states and the District of Columbia had implemented such laws in 2013 [6]. Such comprehensive smoke-free laws have been shown to benefit public health, and may have contributed to declines in SHS-associated conditions such as middle-ear infections, sudden infant death syndrome, and heart disease [2], [14], [15]. More so, in addition to achieving their primary objective of protecting nonsmokers from involuntary SHS exposure, such comprehensive smoke-free laws also denormalize smoking and may motivate smokers to quit.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have examined changes in the volume of hospital admissions with inconclusive results [7]; some show a reduction in hospitalizations for COPD [813], whereas others fail to detect any significant differences [1416]. Similarly, most studies on asthma-related hospital admissions reported a reduction in hospitalizations [10,12,14,1622], but others observed no significant changes [11,15]. …”
Section: Introductionmentioning
confidence: 99%
“…DOI: 10.1161/CIRCULATIONAHA.117.032302 August 7, 2018 563 ORIGINAL RESEARCH ARTICLE larger associations, with cardiovascular events ranging from 25% to 39% lower. 18,20,30,45,46 One potential explanation for the relatively larger magnitude of associations seen in our study is that the study population of the CARDIA cohort includes participants who were enrolled in young adulthood and were at maximum 64 years old at the time of their first cardiovascular event. Several prior ecological studies in the United States and European countries reported stronger relative risks of smoke-free policies with lower rates of hospital admissions among younger people.…”
Section: Original Research Articlementioning
confidence: 90%
“…These findings complement an existing body of literature that has generally indicated that smoke-free policy implementation is associated with lower rates of hospital admissions or mortality for cardiovascular disease. 16,17,[19][20][21][22][27][28][29][30][31][32][33][34][35] Prior studies have typically been ecological in nature [14][15][16][17][18][19][20][22][23][24][25][26][27][28][29][30][31][34][35][36] and have not had access to detailed individual-level information on sociodemographic characteristics and cardiovascular disease risk factors. Our findings that patterns were largely similar after controlling for a large number of potential confounders suggest that differences in cardiovascular disease risk among those in areas with and without smoke-free policies are not explained by differences in individual sociodemographics or traditional cardiovascular disease risk factors.…”
Section: Original Research Articlementioning
confidence: 99%
See 1 more Smart Citation